2021
DOI: 10.1016/j.heliyon.2021.e07487
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of FAO Penman-Monteith and best alternative models for estimating reference evapotranspiration in Bangladesh

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Among the radiation-based methods, Tabari et al [26] reported that the Irmak method performed better than the J-H method under humid conditions in Northern Iran and in other humid regions. Similar results were reported by Pandey et al [25] in Northeastern India and by Islam and Alam [50] in Bangladesh. The FAO24-R method has been shown to outperform the J-R method in the subhumid valley rangeland of the Eastern Himalayas [59], as well as the J-H method under tropical semi-humid conditions in a Brazilian savannah [24].…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…Among the radiation-based methods, Tabari et al [26] reported that the Irmak method performed better than the J-H method under humid conditions in Northern Iran and in other humid regions. Similar results were reported by Pandey et al [25] in Northeastern India and by Islam and Alam [50] in Bangladesh. The FAO24-R method has been shown to outperform the J-R method in the subhumid valley rangeland of the Eastern Himalayas [59], as well as the J-H method under tropical semi-humid conditions in a Brazilian savannah [24].…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
“…Allen et al [9] recommended using linear regression to calibrate the empirical ET 0 methods using the ET 0 values obtained by the FAO56-PM method, and this calibration method has been widely adopted worldwide [35,38,39,[48][49][50]. The calibration process uses the following expression:…”
Section: Calibration Methodsmentioning
confidence: 99%
“…Modified Penman method gave ET0 values nearly closed to the values of FAO-Penman-Monteith values. It was added that the FAO-Penman-Monteith method is the most ideal for ET0 estimation if the involved climatological data are required and the evaporation pan method can be also used, and all factors affecting its records are considered Islam et al, 2021.…”
Section: Reference Evapotranspiration (Eto)mentioning
confidence: 99%
“…Thus to overcome this problem, several scientists and researchers from around the world applied a variety of empirical equations to calculate evapotranspiration (such as the Hargraves, the Blanley Criddle, the Thornthwaite, and the Makkink), but none of them could be deemed flawless due to the vast variations in climatic conditions in different parts of the world (Yates and Strzepe 1994 ; Faruk Bin Poyen et al 2016 ). However, the strong dependence of evaporation on the radiation energy term has been generally accepted (Islam and Rashidul Alam 2021 ; Flores-Velazquez et al 2022 ). Evapotranspiration estimation based on solar radiation measurements eliminates the effect of the surface albedo and minimizes the contribution of the aerodynamic term.…”
Section: Introductionmentioning
confidence: 99%